(Meta)fiction and parody as creative writing: The teaching-learning of Critical Literacy - Ortiz Aguirre, Enrique (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
It seems clear that new approaches to reading and writing are necessary for a society exposed to multimodal literacy and the need for readers to adopt a critical perspective, both because of the simultaneity of codes and because of the overabundance of information and the difficulty of distinguishing true content from false content. In this way, it is a matter of overcoming the conceptions of literacy as a code domain and promoting a polyhedral dimension. The objectives of our study were based on demonstrating the effectiveness of teaching critical literacy as opposed to the traditional models, hegemonic in educational systems.